FINANCIAL PERFORMANCE EVALUATION OF REAL ESTATE COMPANIES IN MALAYSIA: A FUZZY LOGIC APPROACH - Othman, Mahmod; Yeop Yunus, Nek Kamal (International Business Education Journal, 2013)
This paper aims to evaluate the financial performance of the property-related companies in Malaysia using a fuzzy logic approach and provide information of the companies to help investors in a share-investing decision. In this research, the companies in the real estate or property industry are prioritized based on their financial performance using a fuzzy logic approach. The algorithm for the proposed evaluation model consists of three steps: choosing the industries in Bursa Malaysia, choosing the right criteria to select and rank the company’s stock and rank the companies. Finally, the indexes obtained are used to rank the companies. An algorithm is developed and demonstrated in a case study of data on the property industry taken from Bursa Malaysia in 2009. Findings of the research are discussed and future research is recommended.